Associations between a smoke-free homes intervention and childhood admissions to hospital in Scotland: an interrupted time-series analysis of whole-population data. (September 2020) - Turner, Steve; Mackay, Daniel; Dick, Smita; Semple, Sean; Pell, Jill P
Summary: Background: Many children are exposed to second-hand smoke in the home and are at increased risk of asthma and other respiratory conditions. In Scotland, a public health mass-media campaign was launched on March 24, 2014, called Take it Right Outside (TiRO), with a focus on reducing the exposure of children to domestic second-hand smoke. In this study, our aim was to establish whether the TiRO campaign was followed by a decrease in hospital admissions for childhood asthma and other respiratory conditions related to second-hand smoke exposure across Scotland. Methods: For an interrupted time-series analysis, data were obtained on all hospital admissions in Scotland between 2000 and 2018 for children aged younger than 16 years. We studied changes in the monthly incidence of admissions for conditions potentially related to second-hand smoke exposure (asthma, lower respiratory tract infection, bronchiolitis, croup, and acute otitis media) per 1000 children following the 2014 TiRO campaign, while considering national legislation banning smoking in public spaces from 2006. We considered asthma to be the primary condition related to second-hand smoke exposure, with monthly asthma admissions as the primary outcome. Gastroenteritis was included as a control condition. The analysis of asthma admissions considered subgroups stratified by age and area quintile of the Scottish Index of Multiple Deprivations (SIMD). Findings: 740 055 hospital admissions were recorded for children. 138 931 (18·8%) admissions were for respiratory conditions potentially related to second-hand smoke exposure, of which 32 342 (23·3%) were for asthma. After TiRO in 2014, we identified a decrease relative to the underlying trend in the slope of admissions for asthma (−0·48% [–0·85 to −0·12], p=0·0096) in younger children (age <5 years), but not in older children (age 5–15 years). Asthma admissions did not change after TiRO among children 0–15 years of age when data were analysed according to area deprivation quintile. Following the 2006 legislation, independent of TiRO, asthma admissions decreased in both younger children (−0·36% [–0·67 to −0·05], p=0·021) and older children (−0·68% [–1·00 to −0·36], p<0·0001), and in children from the most deprived (SIMD 1; −0·49% [–0·87 to −0·11], p=0·011) and intermediate deprived (SIMD 3; −0·70% [–1·17 to −0·23], p=0·0043) area quintiles, but not in those from the least deprived (SIMD 5) area quintile. Interpretation: Our findings suggest that smoke-free home interventions could be an important tool to reduce asthma admissions in young children, and that smoke-free public space legislation might improve child health for many years, especially in the most deprived communities. Funding: University of Aberdeen Research Excellence Framework 2021 Impact Support Award Scheme.